Evidence for a chimeric nature of nuclear genomes: eubacterial origin of eukaryotic glyceraldehyde-3-phosphate dehydrogenase genes. - Martin, W (1993)
Higher plants process two distinct, nuclear gene-encoded glyceraldehyde-3-phosphate dehydrogenase (GAPDH) proteins, a Calvin-cycle enzyme active within chloroplasts and a glycolytic enzyme active within the cytosol. The gene for the chloroplast enzyme was previously suggested to be of endosymbiotic origin. Since the ancestors of plastids were related to cyanobacteria, we have studied GAPDH genes in the cyanobacterium Anabaena variabilis. Our results confirm that the nuclear gene for higher plant chloroplast GAPDH indeed derives from the genome of a cyanobacterium-like endosymbiont. But two additional GAPDH genes were found in the Anabaena genome and, surprisingly, one of these sequences is very similar to nuclear genes encoding the GAPDH enzyme of glycolysis in plants, animals, and fungi. Evidence that the eukaryotic nuclear genes for glycolytic GAPDH, as well as the Calvin-cycle genes, are of eubacterial origin suggests that eukaryotic genomes are more highly chimeric than previously assumed.